Captured Nazi flag with Steinbeck, Douglas Fairbanks Jr. and others. - Unknown:::Creator::::::::::::
John Steinbeck and captured Nazi flag, with, from top, left to right, Lieutenant Colonel John Cramer, Captain Charles L. Andrews, Lieutenant Commander Douglas Fairbanks, Junior; bottom, Lieutenant Arthur Bryant. These men were members of the Beach Jumpers, Task Group 80.4. Fairbanks was awarded a Silver Star for his actions on Campana, Italy. Steinbeck was armed in this operation, having taken off his correspondent's arm-band. The island had a 114 man German garrison that defended a key radar station. Fairbanks' patrol torpedo boat had offloaded 46 soldiers of the 509th Parachute Infantry Battalion in the night. They met with a local exile from the mainland, who then lied to the German commander that there was a regiment of paratroopers on the island, deposited by a fleet of allied ships. The German commander demolished his own positions and weapons, and then surrendered to the US. No shots were fired. A markedly different version is recounted in an interview with Fairbanks, see John Guttman, 'Specialist in Diversion.' World War II. Fairbanks called the island a radio communications center. On the night of 1943-09-08, loudspeakers warned the enemy troops that a large Allied fleet was offshore and the enemy had 10 minutes to surrender. Fairbanks's group then broadcast decoy sounds and fired nominally into the island to make it seem the 'fleet' was readying for invasion. The Italians quickly indicated surrender. When Fairbanks and a small group landed, German soldiers put up a small fight. The 400 Germans surrendered the night of 1943-09-09.